Sounding prose : music in the 17th-century Dutch novel. - VELDHORST, NATASCHA ([S.l.] : ANTHEM PRESS, 2022)
This book is about the presence of music in novels. More specifically, about music in the early modern novel, with an emphasis on seventeenth-century prose from The Netherlands. The essay provides a concise and an accessible introduction into the subject and presents an overview of this compelling new research area.
Cover -- Half Title -- Title Page -- Copyright Page -- CONTENTS -- FIGURES -- ACKNOWLEDGEMENTS -- 1 INTRODUCTION -- 2 MUSIC IN THE NOVEL BEFORE 1900 -- 3 PROBLEMS STUDYING THE EARLY MODERN NOVEL -- 4 MUSIC AS AN INSERTED GENRE -- 5 MUSIC IN 17TH-CENTURY DUTCH PROSE FICTION -- 6 FUNCTIONS OF MUSIC IN 17TH-CENTURY DUTCH PROSE -- 7 READING NOVELS IN THE 17TH CENTURY -- 8 FICTION AND REALITY -- 9 SINGING WHILE READING -- 10 CONCLUSION -- NOTES -- BIBLIOGRAPHY -- INDEX
JSTOR
Keywords: Dutch fiction -- History and criticism; Dutch literature -- 1500-1800 -- History and criticism; Music in literature; Roman néerlandais -- Histoire et critique; Musique dans la littérature.; History & Criticism; European; LITERARY CRITICISM; Modern; MUSIC; Dutch fiction; Dutch literature; Music in literature; 1500-1800; Criticism, interpretation, etc